2020
DOI: 10.5851/kosfa.2019.e80
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Searing Cooking on Sensory and Physicochemical Properties of Beef Steak

Abstract: The purpose of the present study was to evaluate the sensory and instrumental quality of thawed beef steak prepared by searing and oven cooking. Beef purchased in the local market was divided into two groups; one group was cooked in a 180℃ oven until the internal temperature reached 60℃, and the other group was oven cooked until 35℃, then cooked in a 250℃ pan until the internal temperature reached 60℃. Despite a noticeable change in appearance due to the high temperature of the searing, there was no significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Pyrazines are mainly derived from the Maillard reaction, which requires high temperatures above 110°C in meat [ 26 ], and the formation of these compounds increases at elevated surface temperatures [ 24 ]. Yoo et al [ 27 ] reported that the searing of beef steaks at 250°C increased meaty and roasted aromas compared to oven-cooking 180°C, due to the increased occurrence of the Maillard reaction. Furthermore, 2,3- and 2,5-dimethylpyrazine and methylpyrazine were present in significantly higher quantities in dry-aged beef when cooked by grilling compared to wet-aged beef (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Pyrazines are mainly derived from the Maillard reaction, which requires high temperatures above 110°C in meat [ 26 ], and the formation of these compounds increases at elevated surface temperatures [ 24 ]. Yoo et al [ 27 ] reported that the searing of beef steaks at 250°C increased meaty and roasted aromas compared to oven-cooking 180°C, due to the increased occurrence of the Maillard reaction. Furthermore, 2,3- and 2,5-dimethylpyrazine and methylpyrazine were present in significantly higher quantities in dry-aged beef when cooked by grilling compared to wet-aged beef (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Meat color can provide information about the eating quality of meat to consumers [ 8 ]. For example, browned surface color can be utilized as an indicator of the Maillard reaction and caramelization, and the internal cooked color can indicate the doneness of meat [ 27 , 28 ]. The degree of doneness was further evaluated through a descriptive sensory analysis, as discussed below.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Searing process causes meat surface dehydration, which increases the Maillard reaction development [9,22]. The extent of Maillard reaction development affects the brownness of the meat surface, and consumers generally prefer brown-surfaced steaks or patties rather than those with paler surface [3].…”
Section: Discussionmentioning
confidence: 99%